-5y-4(4y-1)=3-1(3-y)

Simple and best practice solution for -5y-4(4y-1)=3-1(3-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5y-4(4y-1)=3-1(3-y) equation:


Simplifying
-5y + -4(4y + -1) = 3 + -1(3 + -1y)

Reorder the terms:
-5y + -4(-1 + 4y) = 3 + -1(3 + -1y)
-5y + (-1 * -4 + 4y * -4) = 3 + -1(3 + -1y)
-5y + (4 + -16y) = 3 + -1(3 + -1y)

Reorder the terms:
4 + -5y + -16y = 3 + -1(3 + -1y)

Combine like terms: -5y + -16y = -21y
4 + -21y = 3 + -1(3 + -1y)
4 + -21y = 3 + (3 * -1 + -1y * -1)
4 + -21y = 3 + (-3 + 1y)

Combine like terms: 3 + -3 = 0
4 + -21y = 0 + 1y
4 + -21y = 1y

Solving
4 + -21y = 1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
4 + -21y + -1y = 1y + -1y

Combine like terms: -21y + -1y = -22y
4 + -22y = 1y + -1y

Combine like terms: 1y + -1y = 0
4 + -22y = 0

Add '-4' to each side of the equation.
4 + -4 + -22y = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -22y = 0 + -4
-22y = 0 + -4

Combine like terms: 0 + -4 = -4
-22y = -4

Divide each side by '-22'.
y = 0.1818181818

Simplifying
y = 0.1818181818

See similar equations:

| 6x-5x=-105+98 | | z-8/15=2/15 | | .3x+1.5=-3.5x-3 | | (2-7x)=(-4x+8) | | 16y=-11x+13 | | x^2-2x-2kx+2k=0 | | 2(x-4)-(8x+10)=x-14 | | 2x-3=-2x-6 | | 4x-6=14x-8 | | 5-4(5x-3)+8=134 | | 3x-4y+5z=9 | | https://www.vle.mathswatch.com/images/questions/question3802.pn | | 3x-33=21 | | 130=-18-(7y-8) | | 7x-56=5x+10 | | -4x+15=16x+20 | | 4x^2+4x+4=x+3 | | 6x^2-38x=-32 | | 9+u=-3 | | 0=20t+5t^2-125 | | 26=15-(11a+22) | | 30x^2+17*x+2=0 | | 19/20y*5/6x | | 4x+1=9+4x | | 17v-(7v-3)=13 | | X+2=x^2-4x+1 | | 10k-(6k-14)=2 | | -3y-8=16 | | 6x^3-48x= | | .5x+3+2x-12=31 | | 4x-3*3.14=7x+6*3.14 | | 41=48-8(-3-2w) |

Equations solver categories